Iterative learning control with neural network - Li, Jin Yu. (2008)
In this thesis, we will give the proof of the convergence and robustness of the system with off-line NN training algorithm using ILC analysis tools. Further more, we will exploit the on-line implementation and demonstrate the system convergence using Lyapunov approach.